The effects of solvent extracts of Citrulluslanatus seeds and Chrysophyllum albidum cotyledons on rat hepatocyte regeneration, cytochrome c oxidase activities and bacteriocin- producing gram-negative bacteria - Molehin, O. R. (2019)
Medicinal plants have been shown to exert a plethora of biological and pharmacological which has been associated with the presence of several bioactive components. In this study, the effects of crude extracts of Citrullus lanatus seeds (CACL) and Chrysophyllum albidum cotyledons (CACA) on rat hepatocyte regeneration, liver cytochrome c oxidase activities, and their antimicrobial properties on a few bacteriocin-producing Gram-negative bacteria were determined. CACL and CACA were screened for the presence of amino acids using TLC sprayed with ninhydrin, pyridine and modified Commassie brilliant blue (G250). The amino acids were elucidated by Gas Chromatography-Mass Spectrometry (GC/MS) and Fourier-transform infrared spectroscopy (FTIR). CACA enhanced tissue regeneration in rat hepatocytes, in situ and increased the collagen content. CACA also enhanced the activity cytochrome c oxidase in the liver mitochondrial portion, but inhibited same in the homogenate. CACA and CACL did not inhibit the bacteriocin-producing bacteria at the different concentrations tested. It is evident that CACA and CACL contain amino acids that can improve liver antioxidant functions and its mitochondrial electron transport. Both amino acid-rich fractions, combined with bacteriocin may accelerate aseptic wound healing.